2011
DOI: 10.1007/s00330-011-2169-4
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution spiral CT of the breast at very low dose: concept and feasibility considerations

Abstract: Dedicated breast CT may eventually provide comprehensive diagnostic assessment of microcalcifications and soft-tissue structures at dose levels equivalent to or below those of two-view screening mammography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
118
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 24 publications
0
118
0
1
Order By: Relevance
“…The recent development of photon-counting x-ray detectors capable of counting individual photons and sorting them by energy offers unique advantages in tissue characterization. 15,[27][28][29] A proper selection of the energy threshold can minimize the spectral overlap and allow simultaneous acquisition of the dual energy images within a single scan, which eliminates the risks of misregistration.…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of photon-counting x-ray detectors capable of counting individual photons and sorting them by energy offers unique advantages in tissue characterization. 15,[27][28][29] A proper selection of the energy threshold can minimize the spectral overlap and allow simultaneous acquisition of the dual energy images within a single scan, which eliminates the risks of misregistration.…”
Section: Introductionmentioning
confidence: 99%
“…System parameters, including optimized spectra and gantry geometry, have been extensively investigated by several research groups. 25,[27][28][29][30][31][32] An initial clinical study suggests that the cone beam breast CT is significantly better than mammography for visualization of soft tissue lesions. 26 A recent clinical study has also shown that breast CT has a significantly lower anatomical noise than mammography and breast tomosynthesis, providing the ultimate solution to eliminate the anatomical noise induced by overlap of the breast tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Decomposition noise induced by image misregistration or spectral overlap may easily reduce the signal-to-noise ratio to the level where no reliable measurement can be obtained. Recent advances in spectral breast computed tomography (CT) based on energy-resolved photoncounting x-ray detectors offer unique advantages in such imaging tasks (22)(23)(24)(25)(26). Photon-counting detectors are able to count individual photons and sort them according to their energies with a typical energy resolution of a few kiloelectron-volts (27).…”
Section: Methodsmentioning
confidence: 99%